2019
DOI: 10.1111/ecc.13010
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of hope two years after diagnosis of colorectal cancer: Implications for nurse‐led hope programmes

Abstract: Objective To prospectively explore predictors of hope in people with colorectal cancer at 24 months post‐diagnosis. Methods The present study is a secondary analysis of two waves within a longitudinal survey of patients newly diagnosed with colorectal cancer in Queensland, Australia. Baseline predictors (sociodemographic, disease, lifestyle characteristics, cancer threat appraisal and quality of life domains) were measured via mailed surveys and telephone interviews at 6 months post‐diagnosis. Hope was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…In fact, hope predicted the quality of life in these patients. 17 Furthermore, hope was associated with functional, social, and emotional well-being, 18 depression symptoms, 39 depression, and self-esteem 19 in chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, hope predicted the quality of life in these patients. 17 Furthermore, hope was associated with functional, social, and emotional well-being, 18 depression symptoms, 39 depression, and self-esteem 19 in chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the same vein, hope predicted physical activity, disease threat appraisal, and all aspects of quality of life including physical, functional, emotional, and social well-being in chronic diseases such as cancer. 18 On the other hand, pain, depression, self-esteem, and functional status were found to be the predictors of hope in cancer patients. 19 Another study demonstrated that anxiety, depression, effects and symptoms of renal disease, and mental health dimension of quality of life were the predictors of hope in hemodialysis patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The higher levels of depression were also associated with the increased risk of mortality rates in CRC patients 8 . While the previous studies mainly focused on long‐term cancer survivors' depressive levels, 6,7,9 there is an urgent need to identify the associated factors of depression among CRC patients at the transition stage after completing cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has already been claimed to be positively correlated with QoL in adult oncologic patients. 22 Notably, EORTC QLQ-30 surveys in nononcologic women watching Disney movies have never been evaluated, to our knowledge. However, the surprisingly high final QoL in the Disney group might also be associated with the small sample size.…”
Section: Discussionmentioning
confidence: 99%